Carbon based anode materials for Li-ion battery application: a review of recent development - Zahoor, Ahmed; M. A., Hughes; Liew, Josephine Ying Chyi; Talib, Zainal Abidin (Persatuan Sains dan Teknologi Keadaan Pepejal Malaysia, 2021)
Lithium-ion batteries (LIBs) growing energy storage market demand having various carbon-based anodes has attracted much attention as a candidate for high-energy batteries due to its long cycling ability in electric vehicle (EVs) applications. As a part of the electrochemical redox process, excellent anode materials are required to enhance the energy density of the LIBs. Considering it is hard to replace industrial graphitic anodic materials, research focusing on new anode materials having carbon/Si prepared by electrodeposition and sol-gel and its electrochemical performance has been reviewed. Herein, novel carbonaceous and Si/ materials were studied using molten carbonates as an exciting new method of producing graphite composites for lithium-ion battery applications. The electrochemical properties as measured using galvanostatic charge-discharge, cycle ability, rate performance, and cyclic voltammetry were greatly enhanced by using the carbonate-derived anode compared to the commercial graphite. In this review, our focus is on carbon-based anode materials with the recent review of the last five years by compiling literature from 2016-2021.